2022
DOI: 10.3390/su14074061
|View full text |Cite
|
Sign up to set email alerts
|

“Cognition, Intelligence and Movement”: Extracurricular Physical Activity as a Promoter of Intelligence in Schoolchildren

Abstract: The main objective of this study was to assess the existence of significant relationships between motor capacity, academic performance and intelligence in a sample of 67 pre-adolescent children, between the ages of 8 and 11 years. Speed tests were carried out (10 × 5 m shuttle run and plate tapping test), and academic grades in Spanish Language and Literature, Mathematics, Natural Sciences, Foreign Language (English) and Physical Education were considered. The Raven test was administered to estimate the intell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
2
0
1
Order By: Relevance
“…The obtained results reveal statistically significant associations between the analyzed variables, fulfilling the research objective. These findings are in line with previous research that has highlighted the relationships between physical fitness and cognitive functions [23,24,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results reveal statistically significant associations between the analyzed variables, fulfilling the research objective. These findings are in line with previous research that has highlighted the relationships between physical fitness and cognitive functions [23,24,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a study conducted with Chilean students aged 9 to 12 [23] found better results in the gray and color trails test of the Neuropsychological Assessment of Executive Functions Battery for Children (ENFEN) in those students with higher scores in the 20 m shuttle run test, the standing broad jump (SBJ) test, and the 4 m × 10 m shuttle run test from the ALPHA-fitness battery. Another study with students aged 8 to 11 [24] also found associations between cognition and physical activity, assessed through Raven's test and physical speed tests.…”
Section: Introductionmentioning
confidence: 86%
“…Olahraga merupakan kebutuhan bagi manusia dalam kehidupan, agar jasmani dan derajat sehatnya terjaga secara baik (Prasetyo, 2015;Kong, 2019;Real-Pérez, 2022;Volynkina, 2022), peran olahraga dalam menunjang terciptanya sumber energy manusia yang mempunyai kualitas jasmani yang bagus sudah tak diragukan lagi. Kebugaran jasmani adalah sebuah faktor paling utama ketika melakukan suatu aktivitas gerak fisik dengan mempunyai kualitas tubuh yang bugar dan prima maka akan dipastikan sanggup menyelesaikan tugas dengan tanpa terlalu merasa lelah pada tubuhnya atau tidak terlalu berarti, tingkat produktifitas yang baik dapat ditentukan oleh tingkat kebugaran jasmaninya (Saputro, 2018;Davidova, 2020;Man, 2022;Toto, 2019).…”
Section: Pendahuluanunclassified
“…Caring about young immigrants’ integration, acculturation, health and well-being should be on public agents’ agendas. These topics have been addressed in the literature for adults [ 6 , 7 , 8 ], children [ 9 , 10 , 11 ], adolescents [ 12 , 13 ] and households [ 14 ]. However, this work focuses only on studies on young immigrants, analysing the underlying dimensions of a healthy lifestyle—exercise, physical activity and nutrition, among others—and their effects on practising sports.…”
Section: Introductionmentioning
confidence: 99%